Imaging Classification of Exophytic HCC and Our Experience with Microwave Ablation of Type 2 Lesions - Singhal, Soumil; Bhatter, Pallav; Shankar, Girendra; Khandelwal, Anubhav; Baijal, Sanjay Saran (Indian Journal of Radiology and Imaging, 2024)
Purpose The purpose of this article is to classify hepatocellular carcinoma (HCC) based on imaging and to evaluate the role of ultrasound-guided microwave ablation (MWA) in the management of type 2 exophytic HCC.Materials and Methods A retrospective study was performed at our institution after approval by the Institutional Review Board. The study was undertaken from January 2017 to May 2022. Based on the location, HCC was classified and categorized on cross-sectional imaging into four types. All MWA procedures were performed using ultrasound guidance. Patients were followed up every 3 months with cross-sectional imaging.Results During the study period, 225 lesions were reviewed. MWA was performed in 13 type 2 exophytic HCC patients. Segment 3 (38%) was the most common site when categorized as per Couinaud classification and segment 6 was the next common site. Technical success of complete ablation, evaluated by postprocedure contrast-enhanced computed tomography scan, was 100%. The median follow-up period was 24 months (range: 9–24 months). One patient presented with a residual lesion on the first follow-up at 30 days. Two other patients followed up to 9 months were free of HCC. Ten patients followed up at 1 year showed no recurrence, while 7 of them were followed up for 24 months, and 1 of whom showed multicentric recurrence which was treated by selective intra-arterial radiation therapy.Conclusion A classification system for exophytic lesions can allow for better patient selection, planning, and reporting of ablative outcomes. MWA has performed well when ablating these technically challenging lesions with a certain degree of planning.
Keywords: ablation; classification; HCC; microwave ablation